IMPLEMENTASI PEMBELAJARAN ONLINE PADA MATA PELAJARAN KAJIAN KITAB KUNING MASA PANDEMI COVID-19 - Sarihat Sarihat; Eva Syarifatul Jamilah; Maulida Arifatul M (Journal of Research and Thought on Islamic Education (JRTIE), 2020)
Abstract: The aim of this research is to know how to implement a kitab kuning learning media with online system at Middle High School Level (MTs) Darul Qur’an wal Irsyad in pandemic time of COVID-19. As for the type of research that will be used by writers is a nonexperimental quantitative research, with survey research design that trying to explain a quantitative descriptions or numeric description of attitude or opinion tendencies from spesific population by researching one sample from them. Meanwhile the sample that taken in this research is all santri in class VII MTs Darul Qur’an wal Irsyad. The result is to expose based on five (5) component to implement online system learning on studying kitab kuning in MTs Darul Qur’an wal Irsyad, showing that (1) the purpose of learning with this system still achieved, (2) the implementation from learning or component material with online system not achieved yet, (3) the implementation of learning method of this studying still not achieved yet (4) the teacher has attempted the availability of facilities in this kitab kuning learning, right before using online system nor after using it. Yet students still not used to it, (5) the achievement result during online system had not going well. The result of questionnaire in the process of theory and practice in the field was 20% very suitable, 20% suitable, 25% not suitable and 35% very unsuitable/ Keywords: Implementation of Online Learning, Kitab Kuning, COVID-19.